Foreign Investment Contract for Real Estate in the Two Frameworks Conceptual and Structural - Mohammed , Rashid; Alfeel, Nada (Journal of Legal Sciences, 2023)
This study derives its importance from being a research attempt that came to shed light on the conceptual and constructional frameworks of the foreign investment contract for real estate, by clarifying the definitions provided by economic jurisprudence and legal jurisprudence for this contract, identifying its distinctive characteristics and standing on its legal nature, and then revealing the pillars What must be available for its establishment, in order to measure the adequacy of the legislative texts contained in Federal Law No. 19 of 2018 regarding foreign direct investment to face all emerging issues and situations in the real estate investment environment, compared to Egyptian Investment Law No. 72 of 2017, which came Federal Law No. 19 The study resulted in a number of results and recommendations, the most important of which is the call of the UAE legislator to issue a federal law on foreign investment in real estate that includes all legal rules that help the judiciary to find appropriate solutions for all new cases that may appear in the investment environment Real estate in the United Arab Emirates, as a result of the desire of many foreign investors to invest their money every second Peace and tranquility in UAE real estate.